2013
DOI: 10.1093/hmg/ddt601
|View full text |Cite
|
Sign up to set email alerts
|

Expression of alternative oxidase in Drosophila ameliorates diverse phenotypes due to cytochrome oxidase deficiency

Abstract: Mitochondrial dysfunction is a significant factor in human disease, ranging from systemic disorders of childhood to cardiomyopathy, ischaemia and neurodegeneration. Cytochrome oxidase, the terminal enzyme of the mitochondrial respiratory chain, is a frequent target. Lower eukaryotes possess alternative respiratory-chain enzymes that provide non-proton-translocating bypasses for respiratory complexes I (single-subunit reduced nicotinamide adenine dinucleotide dehydrogenases, e.g. Ndi1 from yeast) or III + IV [a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 76 publications
1
77
0
Order By: Relevance
“…Third, most likely as a consequence of constitutive activity, yeast Ndi1 expression can also be deleterious, under conditions where the ATP supply is limiting. This was found to be the case in two Drosophila models of mitochondrial disease, created by the knockdown of complex IV subunits [26] or the tko 25t mutation affecting mitochondrial protein synthesis [32]. Finally, whereas animals such as C. intestinalis have a single NADH dehydrogenase, yeast has three and plants typically several more.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Third, most likely as a consequence of constitutive activity, yeast Ndi1 expression can also be deleterious, under conditions where the ATP supply is limiting. This was found to be the case in two Drosophila models of mitochondrial disease, created by the knockdown of complex IV subunits [26] or the tko 25t mutation affecting mitochondrial protein synthesis [32]. Finally, whereas animals such as C. intestinalis have a single NADH dehydrogenase, yeast has three and plants typically several more.…”
Section: Introductionmentioning
confidence: 93%
“…However, the properties of these alternative NADH dehydrogenases remain uninvestigated, despite an accumulating literature on the alternative respiratory chain of some animals and protozoans, based on our own studies and those of others [25][26][27][28][29][30][31]. Our laboratory has, for example, exploited the alternative oxidase (AOX) from the tunicate Ciona intestinalis to by-pass defects in complexes III and IV, by expressing it in fruit fly [25,26], mouse [27] and human cell [28][29][30] models.…”
Section: Introductionmentioning
confidence: 99%
“…AOX is an alternative electron transport system present in lower eukaryotes, plants and several invertebrates that by-passes the complex III + IV segment of the respiratory chain. Expression of these proteins is well tolerated in mammalian cells [154], flies and mice [155] and has successfully been exploited to by-pass complex I or complex III/IV defects in human cells [156,157] and Drosophila models [158][159][160]. The therapeutic mechanism is based on the capacity of these enzymes to restore the electron flow through the quinone pool, thus preventing accumulation of reduced intermediates and oxidative damage [161].…”
Section: Bypassing the Block Of The Respiratory Chainmentioning
confidence: 99%
“…AOX was targeted to mitochondria and enzymatically active only upon blockade of complex IV: AOX expression enabled bypassing cytochrome c oxidase blockade after cyanide administration without showing deleterious side effects (El-Khoury et al, 2013). In flies, it was shown that AOX can provide a complete or substantial rescue of a range of phenotypes induced by global or tissue-specific knockdown of different complex IV subunits and assembly factors (Kemppainen et al, 2014).…”
Section: Xenotropic Expressionmentioning
confidence: 99%
“…El-Khoury, R., Kemppainen, K.K., Dufour, E., Szibor, M., Jacobs, H.T., and Rustin, P. (2014). Engineering the alternative oxidase gene to better understand and counteract mitochondrial defects: state of the art and perspectives.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%